Pharmaceutical Standardization of Muktashukti Bhasma and Muktashukti Pishti - Kamble, Shweta; Wanjari , Anita (International Journal of Life Science and Pharma Research, 2023)
Shukti is an important component of Sudhavarga, the most recent class in the subject of Rasa Shastra. According to the availability, two forms of Shukti have been stated in Rasa Shastra texts: Jalashukti and Muktashukti. Muktashukti is considered for the study. This study has tried to develop the standard operating process for manufacturing Muktashukti bhasma and Muktashukti pishti. Three batches of MSB & MSP were prepared from the purified Muktashukti. While manufacturing three batches same raw material and manufacturing instruments were used. Before processing for Bhasma or Pishti, the purification process is advocated for Muktashukti. Kanji (Rice gruel) was used for purification as per textual reference. Purified Muktashukti was levigated with Rose water to obtain Pishti. However, for Bhasma preparation, the Muktashukti was triturated with Aloe vera juice, and then heating was done in an Electric muffle furnace. 7 liters of Kanji was taken for 500g of Muktashukti Shodhana by Swedana for 3hrs in Dolayantra, with an average weight rise of 96.24% and a weight loss of 3.76% during the Shodhana method. During MSB preparation, a 10% loss was observed & 90% of Bhasma was obtained. However, in MSP preparation, a 12.14% loss was observed & 87.86% was obtained. This study will give the direction related to the duration of levigation and temperature regulation while Muktashukti Bhasma preparation. For Pishti preparation, the wet grinder was used, which will provide exact rotation and duration to obtain the proper pishti from Muktashukti.